Current advances in mechanical design and production VI : proceedings of the Sixth Cairo University International MDP Conference, Cairo, 2-4 January 1996 - Cairo University International MDP Conference 1996 : Cairo, Egypt); Elarabi, Mohamed E.; Wifi, Abdalla S.; ScienceDirect eBooks (Oxford, U.K. ; Tarrytown, N.Y., U.S.A. : Pergamon, 1996)
The International Conference on Mechanical Design and Production has been established since 1979 by the Department of Mechanical Design and Production at Cairo University. The conference MDP-6 held in Cairo, 2-4 January 1996, represents the 6th in the series. Its aim was to highlight the current advances in mechanical design and production, and to disseminate the latest developments from academic and industrial institutions in all related scientific disciplines. This publication includes a selection of papers submitted to the conference and reviewed by members of the scientific committee. The main areas of the papers include: materials processing and characterization constitutive modeling; simulation and analysis of manufacturing processes; numerical analysis of structures; fracture analysis; design and tribology; dynamics, control and robotics; and new trends in industrial and manufacturing engineering.
Section headings: Honorary Keynote Lecture. Materials Processing and Characterization. Constitutive Modeling. Simulation and Analysis of Manufacturing Processes. Numerical Analysis of Structures. Fracture Analysis. Design and Tribology. Dynamics, Control and Robotics. New Trends in Industrial and Manufacturing Engineering. Author index. Subject index.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Machine design -- Congresses; Materials -- Congresses; Production engineering -- Congresses; Machine design; Materials; Production engineering; Electronic books